Impacto del uso de internet en el aprendizaje significativo del área de informática de los estudiantes del noveno año de educación básica del Colegio Atahualpa de la ciudad de Machala periodo lectivo 2013-2014. - Intriago Vera, Zoila Maricela (2014)
The internet is a tool to which they attribute many advantages for education, commerce, entertainment and last instances, for the development of the individual. Participation in virtual groups, allows us to interact with humans, with our own interests, wherever they are physically located.